2022
DOI: 10.1111/ijag.16611
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fragility maximum in lithium borate glass‐forming melts related to the local structure

Abstract: The structure of liquid lithium pyroborate, Li 4 B 2 O 5 (J = Li/B = 2), has been measured over a wide temperature range by high-energy X-ray diffraction, and compared to that of its glass and borate liquids of other compositions. The results indicate a gradual increase in tetrahedral boron fraction from 3(1)% to 6(1)% during cooling from T = 1271(15) to 721(8) K, consistent with the larger N 4 = 10(1)% found for the glass, and literature 11 B nuclear magnetic resonance measurements. van't Hoff analysis based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Although numerous studies also reported the ADL synthesis and characterization of silicate or borate glasses and melts (for instance, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] ) the strong volatility of some chemical components [48][49][50] (e.g., B 2 O 3 and alkali oxides) under laser irradiation still represents a major drawback of ADL-driven materials discovery, limiting its applicability within these chemical domains. Borate and silicate glasses can be easily prepared by conventional melt-quenching, but ADL was recently shown to provide a superior approach to elucidate transition metal saturation and homogenous nucleation in aluminosilicate glasses and glass-ceramics, [51][52][53] again taking advantage of the high melting temperatures, fast cooling rates and suppression of heterogeneous surface nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies also reported the ADL synthesis and characterization of silicate or borate glasses and melts (for instance, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] ) the strong volatility of some chemical components [48][49][50] (e.g., B 2 O 3 and alkali oxides) under laser irradiation still represents a major drawback of ADL-driven materials discovery, limiting its applicability within these chemical domains. Borate and silicate glasses can be easily prepared by conventional melt-quenching, but ADL was recently shown to provide a superior approach to elucidate transition metal saturation and homogenous nucleation in aluminosilicate glasses and glass-ceramics, [51][52][53] again taking advantage of the high melting temperatures, fast cooling rates and suppression of heterogeneous surface nucleation.…”
Section: Introductionmentioning
confidence: 99%